Foam generation in flow across a sharp permeability transition: Effect of velocity and fractional flow - Shah, S. (Society of Petroleum Engineers, 2019)
Foam reduces gas mobility and can help improve sweep efficiency in an enhanced oil recovery process. For the latter, long-distance foam propagation is crucial. In porous media, strong foam generation requires that local pressure gradient exceeds a critical value (âPmin). Normally, this only happens in the near-well region. Away from wells, these requirements may not be met, and foam propagation is uncertain. It has been shown theoretically that foam can be generated, independent of pressure gradient, during flow across an abrupt increase in permeability (Rossen, 1999). Experimental studies testing the limits of this phenomenon at field-like velocities have not been conducted. The objective of this study is to validate theoretical explanations through experimental evidence and to quantify the effect of fractional flow on this process. This article is an extension of a recent study (Shah et al., 2018) investigating the effect of permeability contrast on this process. In this study the effects of fractional flow and total superficial velocity are described. Coreflood experiments were performed in a cylindrical sintered glass porous medium with two homogeneous layers and a sharp permeability jump in between, representing a lamination or cross-lamination. Unlike previous studies, gas and surfactant solution were co-injected at field-like velocities into a medium at steady-state to gas-brine co-injection. Pressure gradient is measured across several sections of the core. X-ray computerized tomography (CT) is used to generate dynamic phase saturation maps as foam generates and propagates through the core. We investigate the effects of velocity and injected gas fractional flow on foam generation and mobilization by systematically changing these variables through multiple experiments. The core is thoroughly cleaned after each experiment to remove any trapped gas and to ensure no hysteresis. Local pressure measurements and CT-based saturation maps confirm that foam is generated at the permeability transition, which then propagates downstream to the outlet of the core. A significant reduction in gas mobility is observed, even at low superficial velocities, however, the limit of foam propagation is reached at the lowest velocity tested. CT images were used to quantify the accumulation of liquid near the permeability jump, causing local capillary pressure to fall below the critical capillary pressure required for snap-off. This leads to foam generation by snap-off. At the tested fractional flows, no clear trend was observed between foam strength and fg. For a given permeability contrast, foam generation was observed at higher gas fractions than predicted by previous work (Rossen, 1999). Significant fluctuations in pressure gradient accompanied the process of foam generation, indicating a degree of intermittency in the generation rate - probably reflecting cycles of foam generation, dryout, imbibition, and then generation. The intermittency of foam generation was found to increase with decreasing injection velocities and increasing fractional flow. Within the range of conditions tested, the onset of foam generation (identified by the rise in âP and Sg) occurs after roughly the same amount of surfactant injection, independent of fractional flow or injected rate. Copyright 2019, Society of Petroleum Engineers.